PENGARUH JARAK TANAM DAN DOSIS PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KENTANG ( Solanum tuberosum L.) VARIETAS GRANOLA THE EFFECT OF PLANT SPACING AND CHICKEN MANURE OF DOSAGE ON GROWTH AND YIELD OF POTATO PLANT (Solanum tuberosum L. - Fatkur Fatkur; Teguh Supriyadi; Haryuni Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2010)
This Research purposed to know the effect of plant spacing and chicken manure of dosage and interactions to growth and yield of potato plant (Solanum tuberosum L). Research have been done at 22 September to 23 December 2007,in Mlandi village, Subdistrict of Garung Regency of Wonosobo, Province Central of JavaÂ the place height 1.250 m above sea level. The research used factorial method Randomyzed Completely Block Design (RCBD) two treatment, 3 replication, were : 1) The plants spacing (J1 = 60x30 cm, J2 = 70x30 cm, J3 = 80x30 cm). 2) The chicken manure dosage (P1 = 10 ton/ha, P2 = 15 ton/ha, P3 = 20 ton/ha ). The Result of the research : 1) The plants spacing treatment very significant on height of plant, fresh and dry weight of crown per plant, fresh weight and volume of tuber per plant and weight of tuber per plot, but non significant to weight of tuber per plant. 2) The treatment of chicken manure dosage very significant of plant to fresh weight of crown, volume of tuber, weight and total of tuber, and dry weight of crown. 3) Interactions between the plants spacing and chicken manure dosage very significant on the height of plant, dry weight of crown per plant, and total of tuber per plot. But significant to fresh weight of crown, fresh weight and total of tuber also volume of tuber, and total of tuber. 4) The height weight of tuber on combination treatment J2 P3 ( The treatment plant spacing 70x30 cm and chicken manure dosage 20 ton/ha ) was 20,33 kg per plot (31 ton/ha). The lowest weight of tuber on combination treatment J3 P2 ( The treatment plant spacing 80x30 cm and chicken manure dosage 15 ton/ha ) was 10,17 kg per plot (15 ton/ha).